Development of a building energy management system for demand side management - Xu, Bing Yan (2015)
As industrialization and modernization develops over the years, the energy consumption has increased significantly and has resulted in damages to the environment which includes air pollution and global warming. There is growing demand from the society to reduce energy consumption. This project aimed at developing of a building energy management system to monitor and control the electrical loads inside the building in order to achieve energy saving and cost saving. An energy meter was proposed to be integrated to the BEMS to provide real time information of load demand. Various communication protocols were studied and compared for use in the future work for this project. Using demand side management concept in developing the algorithm for the control of the electrical loads like lightings, HVAC system and sump pump, etc., the energy consumption was reduced and cost saving was achieved. The energy meter was successfully integrated into the BEMS to monitor real-time load demand and power consumption. The objectives of this project were met.